Everyday Life and Alienation in Giovanni Giudici’s Poetry - Mozzachiodi, Luca (Scenari, 2023)
The article analyses the development of Giovanni Giudici’s poetic theories and his own poetical works. In his poetry the representation of an alienated everyday life tends to be not only a superficial topic but the specific term of comparison between theorisation and practice. Starting with his first book La vita in versi the exposition combines essays from the two collections La letteratura verso Hiroshima and La dama non cercata with poems and letters to show the different meaning assumed by the poetic description of an ordinary life (as a employed or as a retired old man). Finally the emergence, from late Seventies on, of a spiritualised idea of poetry seen as capable of expressing human integrity against oppression is criticised by showing that Giudici is aware, in his last poems, of the contradiction between the public and collective image of the poet as a special individual and the concrete condition of his life and of poetry as a work rather than a vocation.